Pemilu dan Pilkada dalam Pusaran Politik Identitas - Eka Putra B Santoso (Resolusi: Jurnal Sosial Politik, 2019)
The relationship between politics and religion in Indonesia at this time can be seen from one important thing that is being popularly known, namely politics of identity. Politics of identity is the main spotlight in politics in Indonesia, especially in mainstream and non-mainstream media such as social media. The word politics of identity today can be said to have the same "bad image" as the word politics itself. Especially in Indonesia. Disclosure of certain identities in society in referring to politics seems to be a total mistake and can even be called a grave sin. Like the election of contestants in direct elections based on religion, certain tribes or races become a big disgrace, especially in the midst of the strengthening of Pancasila as an ideology and national identity that should not strengthen at certain times. Remembering Indonesia, which "he said" had agreed with Pancasila. But the phrase politics of identity cannot be denied any more amid the dynamics of current political contestation, with its image as the "big enemy" of the current Pancasila and the main disease of democracy. How is the true identity politics in Indonesia until now, which is said to have strengthened and threatened the integrity of the Unitary Republic of Indonesia? This paper tries to trace the political roots of identity and its development to this day.